A molecular approach to precision medicine in South African children with Epilepsy: towards a genetics-based diagnostic service for Epilepsy - McIntosh, Caitlin (Department of Clinical Laboratory Sciences, 2024)
Background: Epilepsy is a neurological disorder characterised by unprovoked, recurring seizures. SubSaharan Africa carries the highest burden of epilepsy in the world, owing mainly to the increased risk factors such as infectious and parasitic disease, and traumatic brain injury. A proportion of this burden is genetic, however, genetic testing for epilepsy in South Africa is limited, currently only accessible in the private healthcare sector via international referral. Genetic testing in epilepsy is an internationally recognised diagnostic tool which can inform the diagnosis and patient management, with options for precision treatment, frequently resulting in improved outcomes. The main aim of this research project, therefore, was to design and validate a next-generation sequencing (NGS) gene panel for South African paediatric patients with drug-resistant epilepsy. The panel design was aimed primarily at the developmental and epileptic encephalopathies, where the yield of informative findings is highest, and the results often carry implications for treatment. The secondary aim of the project was to perform preliminary pharmacogenetic testing, to determine if variants previously associated with antiseizure drug metabolism in other populations are present in this study group. Materials and Methods: Forty probands with clinically complex, drug-resistant epilepsy with no identified, acquired cause were recruited from the neurology epilepsy service at the Red Cross War Memorial Children's Hospital in Cape Town. All 40 probands were tested with a panel of 78 genes selected on the basis of association with disease and clinical actionability. NGS data files were subject to variant prioritisation, followed by variant confirmation by cycle sequencing, segregation analysis, and final classification according to ACMG criteria. All 40 probands were tested with two pharmacogenomic arrays, one generalised array, the Veridose® Core Panel produced by Agena Bioscience (San Diego, USA), and one custom-designed anti-seizure medication-specific SNV array targeting eight SNVs across six different genes. Results: Three pathogenic variants were identified; two in SCN1A and one in GRIN2A, with a pickup rate of 7.5% (3/40). Two variants of uncertain significance were identified in GABRG2 and GRIN2B. The findings were aligned with the electroclinical features in each patient. The pharmacogenomic analysis revealed one variant, EPHX1 rs1051740, which appeared to be statistically significantly differently distributed in the study group to the general African population (P = 0.02). Three other variants, EPHX1 rs2234922, SCN1A rs3812718, and CYP2d6 s59421388 appear to be trending towards significance, with P-values of 0.08, 0.05, and 0.05, respectively. Conclusion: The main outcome of this project was the successful development of an NGS-based diagnostic protocol for paediatric epilepsy using the gene panel approach, now ready for implementation in the local diagnostic testing laboratory. Moreover, the genetic cause of epilepsy was identified in three study participants, with treatment implications in two (variants in SCN1A). The pharmacogenomic analysis in this project did not reveal specific insights owing to the small study group, but provided exposure to pharmacogenomic analysis, and may be used as a basis for further research into the pharmacogenomics of epilepsy in larger African cohorts.